UTILIZAÇÃO DA TECNOLOGIA DE DEPOSIÇÃO SUPERFICIAL POR ATRITO (FRICTION SURFACING) PARA PRODUÇÃO DE DEPÓSITOS DE LIGA AA6351-T6 PREENCHIDA COM PARTÍCULAS DE ALUMINA SOBRE UMA LIGA AA5052-H32. - Oliveira, Pedro Henrique Fernandes (2016)
The aim of this study was to produce deposit of the alloy AA 6351-T6, filled with alumina particles, on an AA5052-32 alloy substrate using friction-surfacing technology. The depositions were performed with holes in the AA6351-T6 consumable rods, which were filled with particulate alumina (Al2O3). A conventional milling machine, KONE KFE-3 / BR, available by SENAI Ponta Grossa – Paraná, was used to carry out the deposition. The control parameter used for the making the deposits was the rod feed rate being calculated from the relationship between the upward axial displacement in the Z axis (Dz) of the machine table and the total time (t) of deposition. The deposits obtained were evaluated from their physical aspects such as width, thickness and length. In addition, bending tests were conducted for a qualitative assessment of the influence of the alumina particles in the adhesion of the deposit to the substrate and microhardness profiles were obtained to evaluate the influence of the alumina particles produced in the hardness of the deposits. Images of optical microscopy images (OM) and scanning electron microscopy (SEM) were obtained to evaluate the microstructure and morphology of the deposits produced. The volume fraction of alumina particles in the deposits were obtained by digital processing of the images by optical microscopy. EBSD analysis of deposits in specific regions were performed in order to support the microstructural analysis, enabling verify grain size distribution in different regions of deposits showing the existence of substructures indicating the occurrence of dynamic recrystallization phenomenon. The results showed that it was possible to produce deposits with a refined microstructure and with a certain dispersion of alumina particles. Depositions with two holes in the rod produced deposits with higher volume fraction, and this increase in volume fraction was accompanied by higher hardness values.